Administration of rectal cytotec versus rectal buscopan before hysteroscopy. Issue 1 (3rd January 2022) - Gokmen Karasu, Ayse Filiz; Aydin, Serdar; Ates, Seda; Takmaz, Taha; Comba, Cihan
Abstract: Introduction: Our objective was to compare the effect of rectal misoprostol (Cytotec) versus rectal hyoscine-n-butyl bromide (Buscopan) on patients undergoing hysteroscopy. We hypothesised that HBB may have a role in cervical priming. Material and methods: This trial was conducted at Bezmialem Vakif University Hospital. Women of reproductive age between 18–50 years who were scheduled for operative hysteroscopy indicated by type 1 submucous myoma or endometrial polyps were recruited for the study. Ninety patients were divided randomly into three groups. Group 1 received placebo treatment. Group 2 received rectal 200 mcg misoprostol and Group 3 received rectal 20 mg hyoscine-n-butyl bromide two hours before the procedure. Procedures were performed using a bipolar 26 F (9 mm) continuous-flow rigid resectoscope with a 30° lens. The outcome measures included cervical dilation width and time, ease of cervical dilation, procedure time and operative complications. Postoperative self-rated pain was assessed one hour after the procedure. Results: Thirteen patients (43. 3%) in the placebo treatment group, 11 patients (36.7%) in the misoprostol group and four patients (13.3%) in the hyoscine-n-butyl bromide group needed analgesics postoperatively ( p = .02). The mean duration of cervical dilation time was longest in Group 1 and shortest in Group 3, however this difference did not reach statistical significance ( p =.11). There was no difference with regard to other studied parameters. Summary: HBB reduced the need for pain medication compared to placebo. Larger studies are needed to further investigate the role of HBB in facilitating pre-operative cervical priming.